Positive Impulse Phase versus Propulsive Impulse Phase: Correlations between Asymmetry and Countermovement Jump Performance - Keith B. Painter; William Guy Hornsby; Kevin Carroll; Satoshi Mizuguchi; Michael H. Stone (Journal of Functional Morphology and Kinesiology, 2022)
The relationship between asymmetry and performance is still undetermined in the literature. Methods of assessing asymmetry have been inconsistent and focused on the analysis of jumping asymmetry. Dual ground reaction forces are prevalent in athlete monitoring, though underutilized in asymmetry research. The purpose of this study was to assess the relationship of countermovement jump (CMJ) impulse asymmetry to performance in collegiate soccer athletes. Male and female athletes were selected from an ongoing athlete research repository database of NCAA D-I soccer athletes. All athletes contributed two maximal effort unweighted (CMJ0) and weighted countermovement jumps (CMJ20) using the mean for calculations. Propulsive phase asymmetry scores (PrPAS) and positive impulse asymmetry scores (PIAS) were calculated to determine the magnitude of asymmetry for each prospective phase. Statistically significant correlations were found between CMJ0 jump height and unweighted PIAS (r = −0.43) in females. Males had statistically significant correlations between CMJ20 jump height and weighted PIAS (r = −0.49). Neither unweighted PrPAS nor weighted PrPAS produced statistically significant correlations (r < 0.26) to their prospective jump heights. When assessing CMJ asymmetry, it is recommended to conduct both weighted and unweighted CMJ testing, utilizing PIAS as the metric to be assessed.